How has the 'customary nature' of Japanese fisheries reacted to Covid-19? An interdisciplinary study examining the impacts of the pandemic in 2020. (April 2022) - Sugimoto, Aoi; Roman, Raphael; Hori, Juri; Tamura, Norie; Watari, Shingo; Makino, Mitsutaku
Abstract: Like many other countries, the economy and society of Japan have been deeply affected by the Covid-19 outbreak, and the fishery sector is no exception. This study takes an interdisciplinary approach to analyze the economic and social impacts of the pandemic on Japanese fisheries, gauging the extent and nature of the damages incurred from Covid-19 while helping to provide tailored post-recovery recommendations for the industry. Using results from an online survey questionnaire (N = 429) and compiling additional economic information from public sources, this study revealed the overwhelmingly negative changes in sales figures and overall financial security that survey participants experienced when compared to a year earlier. High-value and fresh fish species were also significantly affected in 2020 across Japan, in line with similar trends across the developed world. Aquaculture businesses were shown to be more vulnerable to the spread of Covid-19 than small-scale fishing operations, which tend to be more diverse and flexible. Bonding social capital was also shown to be important for mutual help and human well-being, especially among small-scale fishers. This "customary nature" of Japanese fisheries, at the same time, can be seen as a barrier to the transformation of the industry. Given these results, several policy implications are discussed to help fisheries stakeholders and their communities build back better from the Covid-19 pandemic. Graphical Abstract: ga1